Late Pleistocene cryogenesis features of a loess-paleosol sequence in the Srednyaya Akhtuba reference section, Lower Volga river valley, Russia. (20th July 2021) - Taratunina, N.; Rogov, V.; Streletskaya, I.; Thomson, W.; Kurchatova, A.; Yanina, T.; Kurbanov, R.
Abstract: Permafrost is considered to be one of the important sources of additional water for the vast Late Quaternary Caspian Sea transgressions. The insufficiency of proxy evidence on landscape and climate dynamics during the long Atelian regression (MIS 4 – MIS 3) complicates the analysis of changes in the Caspian water balance. Traces of Late Pleistocene cryogenesis structures were catalogued in the alluvial and loess-soil deposits of the Srednyaya Akhtuba reference section. Four stages of permafrost development were described for the first time in the Lower Volga region. Under conditions of seasonal and longer-term freezing in the Late Pleistocene, cryogenic transformation of the deposits took place; this determined the composition, structure and properties of the loess-paleosol complex at the site. Cryolithological, micromorphological analyzes and particle size distribution of mineral matter were carried out for each horizon, and traces of cryogenic processes were described in order to evaluate the regional paleoclimatic conditions that prevailed during their formation. Optically stimulated luminescence dating was used to establish a chronological framework for the main phases of the development of cryogenic modification in the Lower Volga region. The fourth stage of formation involved deep cracking of the substrate, which occurred during freezing in MIS 4, coincident with the Atelian regression of the Caspian Sea. The third stage is expressed as large wedge-shaped structures (pseudomorphs) on the border of loess and alluvial packages, with their formation known to be associated with the degradation of ice wedges. During the second and first stages of freezing, plastic deformation of deposits occurred.